Pembingkaian Pemberitaan Kasus Pungutan Liar Kepada Guru Asn Pangandaran Dalam Media Detik.Com Dan Kompas.Com (Kajian Framing Zongdan Pan & Gerald M. Kosicki) - Abdu Maulana Arrasyid Maulana Arrasyid; Hendra Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The development of science and technology makes human life change, these changes include various things including information. The mass media, which used to only use print media such as newspapers, now uses the internet to convey information. The role of the media in providing information has an important role in society. Each media has its own characteristics in presenting its news. In this research, we will examine how the mass media present their news and package it in such a way that it becomes objective and interesting information. In this study, Zhongdan Pan & Gerald M. Kosicki's framing analysis model becomes the theory used to analyze Detik.com and Kompas.com media. The aspects studied are syntactic structure, script, thematic, and rhetorical. The results of the study show that the Detik.com media focuses on reporting how the response and statement from the head of the Pangandaran District BKPSDM regarding alleged illegal levies, while Kompas.com focuses on how the chronology of events came to the attention of the public and explains what incidents the victim experienced then what the response was from Head of BKPSDM Pangandaran Regency for alleged cases of extortion and intimidation.